The Effect of the Project Based Learning Model on Student Science Learning Outcomes - Takndare, Maria Margaretha Terunenan; Adnan, Adnan; Nurhayati, Nurhayati (Borong Newinera Publisher, 2024)
To determine the effect of the PjBL model on the learning outcomes of grade VII students of SMP Negeri 2 Barombong, Gowa Regency. This research uses quasi-experimental methods. The place of research is carried out at SMP Negeri 2 Barombong, Jl. Poros Kanjilo No. 11, Kanjilo Village, Barombong District, Gowa Regency. The results showed that the students' abilities were in the medium category. This research indicates a significant influence of the application of the project-based learning model on student learning outcomes. The project-based learning model is able to provide a more interactive and immersive learning experience, which in turn has a positive impact on student academic achievement.